Bolus epidural infusion improves spread compared with continuous infusion in a cadaveric porcine spine model. Issue 12 (27th September 2019) - Cole, Jacob; Hughey, Scott
Abstract : Background: The administration of epidural anesthesia during labor is a common technique used to reduce the pain of childbirth. We sought to compare standard infusion strategies of continuous epidural infusions (CEI) with programmed intermittent epidural bolus (PIEB) to assess the length of spread in terms of vertebral body length. Based on previous clinical data in humans, the PIEB was associated with improved pain control and decreased total dose of local anesthetic. We hypothesized that the PIEB was associated with increased spread when compared with CEI. Methods: Thirty female Yorkshire-cross swine cadavers were used to compare three infusion strategies, continuous infusion (CEI) 10 mL/hour programmed continuously, multiple bolus (MB) 2 mL given every 12 min for 10 mL total and 10 mL delivered in a single bolus (SB). Radiographs were used to identify the spread of the radiopaque contrast dye, and a number of vertebral bodies covered were measured to assess spread. Results: Overall, the CEI had an average spread of 5.6 levels, MB 7.9 and SB 10.4. The differences between SB and MB (p=0.011), SB and CEI (p<0.001) and MB and CEI (p=0.028) were all found to be significant. Conclusions: We demonstrated increased spread of epidural contrast with programmed intermittent bolus strategies. This supports previous evidence of improved patient outcomes with PIEB strategy compared with CEI, and encourages the use of PIEB in the appropriate patient population.